Media and climate justice: what space for alternative discourses? - Carvalho, Anabela (2018)
Preprint version of book chapter - To appear in: K.-K Bhavnani, J. Foran, P. A. Kurian & D. Munshi (eds) Climate Futures: Re-imagining Global Climate Justice, University of California Press